2021
DOI: 10.21608/sjfop.2021.211809
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Water Regime Treatments on Growth of Rosmarinus Officinalis L. Plant

Abstract: The current research was carried out at the Hort. Dept., Fac. of Agric., Benha Univ., Egypt, throughout the 2019/2020 and 2020/2021 seasons. To investigate the impact of water regime i.e. (100, 70 and 50% of field capacity) on growth of Rosmarinus officinalis L. plant in the two seasons. The results revealed that differences treatments of field capacity increased the growth parameters of rosemary plant in the two seasons. The use of field capacity at 100% achieved the highest values on all studied parameters o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(13 reference statements)
1
0
0
Order By: Relevance
“…It was clear that irrigation at 100% ETc was the most effective treatment in this concern. Our results are line with Agina et al (2021) on rosemary. The positive impact of glutamic acid on macro and micro nutrients in plants indicated that, spraying with glutamic acid at 10mM led to maximum increase of N, P, K, Cu and Fe by 35.79 and 34.05%, 50 and 40%, 35.38 and 39.53%, 32.88 and 30.92%& 37.13 and 31.79% for 1 st and 2 nd cuts, respectively of the first season as compared to untreated plants (Table 10 and 11).…”
Section: The Macro and Micro-nutrients Contentsupporting
confidence: 91%
“…It was clear that irrigation at 100% ETc was the most effective treatment in this concern. Our results are line with Agina et al (2021) on rosemary. The positive impact of glutamic acid on macro and micro nutrients in plants indicated that, spraying with glutamic acid at 10mM led to maximum increase of N, P, K, Cu and Fe by 35.79 and 34.05%, 50 and 40%, 35.38 and 39.53%, 32.88 and 30.92%& 37.13 and 31.79% for 1 st and 2 nd cuts, respectively of the first season as compared to untreated plants (Table 10 and 11).…”
Section: The Macro and Micro-nutrients Contentsupporting
confidence: 91%